Penyuluhan Hipertensi dan Senam Lansia sebagai Upaya Peningkatan Kebugaran Lansia Pasien Hipertensi - Raden Ayu Tanzila; Ni Made Elva Mayasari; Miranti Dwi Hartanti; Syabila Azzahra; Diva Syaidatun (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Hypertension is a major risk factor for cardiovascular disease, commonly affecting the elderly. Hypertension education and elderly exercise programs serve as effective interventions to enhance elderly individuals' understanding of hypertension while improving their physical fitness. This community service program aims to assess the effectiveness of elderly exercise and hypertension education in raising awareness, enhancing knowledge, and lowering blood pressure among hypertensive elderly individuals. The method involved a structured elderly exercise routine conducted over one month alongside interactive health education on hypertension. The activity involved 32 participants who met the inclusion and exclusion criteria. The program was conducted for one month in October 2024 at the Family Doctor Clinic, Faculty of Medicine, Universitas Muhammadiyah Palembang. Blood pressure measurements and pre-test and post-test assessments were taken before and after the program to evaluate knowledge improvement. The results showed a significant reduction in both systolic and diastolic blood pressure after participating in the program (p < 0.05). Additionally, pre-test and post-test results indicated a significant improvement in participants' understanding of hypertension. This program demonstrates that combining health education with physical activity positively impacts blood pressure control and elderly fitness. Therefore, it is recommended that this program be implemented regularly in community settings to promote sustainable elderly health.